Evaluation of the Strategy in Cooperative and Small-Medium Enterprise Department for Effective Members' Meeting Implementation: An Educational Perspective - Tsurayya Annisa; Rizki Syafril (Nurul Jadid University, 2025)
This study aims to evaluate the strategies implemented by the Cooperative and Small-Medium Enterprise (SME) Department in organizing effective members' meetings, with a focus on educational aspects. The research seeks to assess how these strategies impact members' engagement, understanding, and participation, as well as their alignment with academic goals for cooperative development. The research employs a qualitative approach, utilizing interviews and document analysis to gather data from key stakeholders involved in the planning and execution of members' meetings. The data are then analyzed through thematic analysis to identify key patterns and insights. The findings indicate that while the strategies are generally effective in fostering engagement, there are significant gaps in the educational elements of the meetings. Members often lack a sufficient understanding of the cooperative's educational objectives, hindering the cooperative's long-term development. Furthermore, there is a need for more structured educational interventions during meetings. The implications of this study suggest that enhancing the educational content and delivery of members' meetings can improve cooperative members' skills and knowledge, fostering better decision-making and sustainable growth. Educational strategies should be integrated more systematically into the meeting framework to maximize their impac